Detection of Transitions between Dwarf Nova Outbursts, Standstills, and IW And–type Cycles - Qi-Bin Sun; Sheng-Bang Qian; Li-Ying Zhu; Qin-Mei Li; Wen-Ping Liao; Fu-Xing Li; Wen-Xu Lin; Min-Yu Li; Ping Li (The Astrophysical Journal)
IW And–type objects represent a rare and intriguing subclass of cataclysmic variables that challenge the classical disk instability model. Due to their long timescales, often lasting several months, observed samples are scarce, leaving the physics of state transitions poorly understood. Here, we report the discovery of ASASSN-V J175721.00+152502.1 as a new IW And–type system based on both ground-based and space-based survey data. For the first time, we measure its orbital period and negative superhump (NSH) period as 0.25619(81) days and 0.24107(33) days, respectively. We present detailed observational evidence for transitions between IW And–type cycles, classical standstills, and normal dwarf nova outbursts. Notably, the transition from the IW And–type cycle to a classical standstill is presented in detail for the first time, together with a decrease in the NSH period, which provides evidence for accretion disk expansion. We evaluate theoretical models that could explain the observed light variations and rule out simple scenarios such as mass-transfer bursts or superoutbursts. Although the tilted-disk thermal instability model is the most plausible, it does not fully account for the detailed behavior. We propose that a combination of factors, such as thermal-viscous instabilities, fluctuations in the mass-transfer rate, changes in the disk radius, tilted disk precession, and tidal dissipation involving the secondary star, is likely needed to explain the full range of observed phenomena.